Information Sharing, Trust, and Competitive Advantage: Impact on Business Performance in Plasma Farmer Groups - Lailan Tawila Berampu; Riri Liardini Putri Anjani; Andewi Rokhmawati; Taufiqurrahman (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Plasma farmer groups smallholder farmers linked contractually to larger nucleus companies in the palm oil industry face challenges in maintaining consistent fresh fruit bunch (FFB) quality. These challenges, primarily due to the use of uncertified seeds and fluctuating yields, negatively affect their business performance. To address these issues, this study investigates how information sharing and trust influence business performance, both directly and indirectly, through competitive advantage. A quantitative approach was adopted using a five-point Likert-scale questionnaire administered to 83 plasma farmer groups selected through probability sampling. Structural equation modeling via SmartPLS was used to analyze the data. Results show that both information sharing and trust significantly enhance business performance, directly and via competitive advantage. Effective information sharing improves coordination and operational efficiency, while trust strengthens reliable partnerships, leading to higher productivity and profitability. Competitive advantage achieved through superior product quality and cost efficiency amplifies these effects. The study concludes that fostering transparent communication and trust-based collaboration is critical to strengthening the competitiveness and sustainability of plasma farmer groups within the palm oil supply chain.